Discipline, Promotion, and Compensation Strategies to Enhance Employee Performance at the Pekalongan Health Department - Sinta Damayanti; Husna Amniyati (Journal of Economic Perspectives and Business Innovation, 2024)
Abstract This study aims to analyze the influence of discipline, promotion, and compensation strategies on employee performance at the Pekalongan Health Department. Employee performance is a crucial factor in achieving effective public service delivery, particularly in the health sector. This research adopts a quantitative descriptive approach, utilizing data collected through questionnaires distributed to employees of the Pekalongan Health Department. The results indicate that work discipline significantly affects employee performance by improving responsibility, punctuality, and compliance with organizational regulations. Promotion opportunities are found to motivate employees to enhance their skills and work productivity. Meanwhile, fair and appropriate compensation contributes to increased job satisfaction and work commitment. Simultaneously, discipline, promotion, and compensation have a positive and significant impact on employee performance. The study concludes that the implementation of integrated human resource management strategies is essential to improve employee performance and organizational effectiveness in the public health sector. Keywords work discipline, promotion, compensation, employee performance, public sector